Two new species of the genus Cordilura Fallén, 1810 (Diptera, Scathophagidae) from the Russian Far East - Ozerov, A.l.; Krivosheina, M.g. (Zootaxa, 2015)
Cordilura Fallén, 1810 is one of the largest genera within the family Scathophagidae. According to new species descriptions and recent catalogues (e.g. Šifner, 2008), the genus currently comprises 86 species in the World distributed primarily in the Holarctic Region: 50 species are known in Palaearctic and 43 in Nearctic, with 7 species with a Holarctic distribution; and other 2 species are recorded in Oriental Region (Ozerov & Krivosheina, 2012a; 2013). In Russia, 33 species are known, 25 of them in the Russian Far East (Ozerov & Krivosheina, 2014).